Idelalisib induced drug toxicity presenting as drug induced pneumonitis: a case report - Verma, Sameer; Pandya, Dhwani; Khanijo, Sameer; Esposito, Michael; Talwar, Arunabh (International Journal of Advances in Medicine, 2021)
Idelalisib is a novel treatment option for patients with chronic lymphocytic leukemia. A rare, but, fatal complication of using Idelalsib is drug induced pneumonitis. This article presents a case of Idelalsib induced pneumonitis in a patient with chronic lymphocytic leukemia along with a brief discussion of management plan.